Mengungkap realitas penghapusan piutang kedaluwarsa terhadap pajak bumi dan bangunan perdesaan dan perkotaan di Kabupaten Tanah Bumbu - Yuyun Yuniar; Sarwani; Novika Rosari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research aims to analyze the mechanism for writing off expired rural and urban land and building tax receivables in relation to available regulations, and the factors behind writing off expired rural and urban land and building tax receivables. The research method uses descriptive qualitative methods with a phenomenological approach. The research object was the Regional Work Unit, namely the Tanah Bumbu Regency Regional Revenue Agency, while the sample used a purposive sampling technique of 20 informants who came from the government's internal Regional and External Revenue Agency as well as elements of the village and community. The results of the research show that the Regional Revenue Agency of Tanah Bumbu Regency implemented the write-off of expired receivables for Rural and Urban Land and Building Tax to update receivables data aimed at fulfilling the accurate presentation of tax receivables data in reliable financial reports. The implication of the research is that regulations related to the mechanism for writing off expired receivables against PBB P2 will be used as a basis for guidance for other regional governments in implementing procedures for writing off expired receivables against PBB P2 to improve regional tax receivables data which is still considered waste data.